PMR6, a Pectate Lyase–Like Gene Required for Powdery Mildew Susceptibility in Arabidopsis - Vogel, John P. (American Society of Plant Biologists, 2002)
The plant genes required for the growth and reproduction of plant pathogens are largely unknown. In an effort to identify these genes, we isolated Arabidopsis mutants that do not support the normal growth of the powdery mildew pathogen Erysiphe cichoracearum. Here, we report on the cloning and characterization of one of these genes, PMR6. PMR6 encodes a pectate lyase–like protein with a novel C-terminal domain. Consistent with its predicted gene function, mutations in PMR6 alter the composition of the plant cell wall, as shown by Fourier transform infrared spectroscopy. pmr6-mediated resistance requires neither salicylic acid nor the ability to perceive jasmonic acid or ethylene, indicating that the resistance mechanism does not require the activation of well-described defense pathways. Thus, pmr6 resistance represents a novel form of disease resistance based on the loss of a gene required during a compatible interaction rather than the activation of known host defense pathways.